PROFESSIONAL TRAINING OF THE TEACHER FOR THE ORGANIZATION OF RESEARCH ACTIVITIES IN THE EDUCATIONAL PROCESS - Ye.S. Dehtyar (Academy of Cognitive and Natural Sciences, 2009)
The article deals with the theoretical foundations of problem of preparation of teacher to the organisation of the research activity in the educational process. The article ground importance and peculiarity of usage of the research methods in the educational and upbringing process.